NU HOUSING MANAGEMENT SYSTEM - Balgali, Almaz; Kozhamuratov, Nurzhan; Kurasbek, Dana; Nussipbekov, Nurbek; Yeltay, Adi (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Throughout this semester, we have been developing the Housing Management System (HMS) requested by the University Service Management (USM). The problem to be solved was to develop a modernized version of an outdated HMS that collects all information into a single system; currently, USM has several Excel files with tens of unstructured sheets storing tenants data. Key objectives include developing a new system with flexible report generation features. To develop this new system, we read several secondary resources to identify the key features every HMS should have. Secondly, we conducted primary research by repeatedly interviewing the stakeholders (i.e., USM, DSS staff) to get a better understanding of the system and collect requirements. Overall, for the development process, we used an agile incremental approach since we communicated closely with stakeholders and adjusted the system accordingly. We also used Trello for task management, sprint planning, and team collaboration. Finally, we used different testing methods to evaluate our system. As a result, as mentioned above, we built a web-based application, which has eliminated the need for multiple Excel sheets. The system also provides automated report generation supporting both filter-based reports (e.g., tenants by building) and chat-based reports, where the user types their queries or prompts (e.g., “show tenants who have pets”). This new HMS makes USM workers’ work easier and saves their time.
Keywords: Housing Management System (HMS); type of access: open access